The Role Of Destination Image In Tourist Destination Branding (Case Study: Lattakia Governorate) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to determine the role of tourist destination image in destination branding, by building a conceptual model for converting the tourist destination into a brand in order to use it as a competitive tool that distinguishes Lattakia Governorate from other tourist destinations. To achieve this purpose, a field study was conducted that relied on directing a questionnaire to a purposeful (intentional) sample of local and foreign tourists who visited Lattakia Governorate in the summer of 2021, where (240) questionnaires were distributed to them, of which (228) were valid for statistical analysis. The study reached a set of results, the most important of which is the existence of a significant relationship between the cognitive image and the emotional image of the tourist destination on the one hand, and the general image formed by the tourist about this destination on the other hand. The results also showed the existence of clear and significant relationships between the general image of the tourist destination and the dimensions of converting that destination into a brand (destination choice, intention to re-visit the destination, recommending the destination), where the largest impact of the image of the destination on the tourist's choice appeared. The study also found the possibility of applying the concept of tourist destination branding in Lattakia Governorate, by working on forming a positive mental image of that destination that contributes to a positive impact on the behavior of the tourist.